An Institution of Corporate Social Responsibility (CSR) in Multi-National Corporations (MNCs): Form and Implications - Bondy, Krista; Moon, Jeremy 1955-; Matten, Dirk 1965- (2012)
This article investigates corporate social responsibility (CSR) as an institution within UK multi-national corporations (MNCs). In the context of the literature on the institutionalization of CSR and on critical CSR, it presents two main findings. First, it contributes to the CSR mainstream literature by confirming that CSR has not only become institutionalized in society but that a form of this institution is also present within MNCs. Secondly, it contributes to the critical CSR literature by suggesting that unlike broader notions of CSR shared between multiple stakeholders, MNCs practise a form of CSR that undermines the broader stakeholder concept. By increasingly focusing on strategic forms of CSR activity, MNCs are moving away from a societal understanding of CSR that focuses on redressing the impacts of their operations through stakeholder concerns, back to any activity that supports traditional business imperatives. The implications of this shift are considered using institutional theory to evaluate macro-institutional pressures for CSR activity and the agency of powerful incumbents in the contested field of CSR.
Keywords: Business Case; Institutional Theory; Multi-national corporations; critical perspectives; Corporate Social Responsibility